Effect of Land-Based Generic Physical Activity Interventions on Pain, Physical Function, and Physical Performance in Hip and Knee Osteoarthritis: A Systematic Review and Meta-Analysis. (November 2017) - Fernandopulle, Shanelle; Perry, Meredith; Manlapaz, Donald; Jayakaran, Prasath
Abstract : Objective: The aim of this study was to evaluate the effects of land-based generic physical activity interventions on pain, physical function, and physical performance in individuals with hip/knee osteoarthritis, when compared with a control group that received no intervention, minimal intervention, or usual care. Methods: A systematic search for randomized controlled trials on 11 electronic databases (from their inception up until April 30, 2016) identified 27 relevant articles. According to the compendium of physical activities, interventions were categorized into: recreational activities (tai chi/Baduajin—6 articles), walking (9 articles), and conditioning exercise (12 articles). Results: Meta-analysis for recreational activity ( n = 3) demonstrated significant mean difference (MD) of −9.56 (95% confidence interval [CI], −13.95 to −5.17) for physical function (Western Ontario and McMaster Universities Arthritis Index) at 3 mos from randomization. Pooled estimate for walking intervention was not significant for pain intensity and physical performance but was significant for physical function ( n = 2) with a MD of −10.38 (95% CI, −12.27 to −8.48) at 6 mos. Meta-analysis for conditioning exercise was significant for physical function ( n = 3) with a MD of −3.74 (95% CI, −5.70 to −1.78) and physical performance (6-minute walk test) with a MD of 42.72 m (95% CI, 27.78, 57.66) at 6 mos. The timed stair-climbing test ( n = 2) demonstrated a significant effect at 18 mos with a MD of −0.49 secs (95% CI, −0.75 to −0.23). Conclusion: Very limited evidence to support recreational activity and walking intervention was found for knee osteoarthritis, in the short-term on pain and physical function, respectively. Abstract : Supplemental digital content is available in the text.